Pacemaker implantation after sutureless or stented valve: results from a controlled randomized trial. (15th March 2022) - Lorusso, Roberto; Ravaux, Justine M; Pollari, Francesco; Folliguet, Thierry A; Kappert, Utz; Meuris, Bart; Shrestha, Malakh L; Roselli, Eric E; Bonaros, Nikolaos; Fabre, Olivier; Corbi, Pierre; Troise, Giovanni; et al.
Abstract: OBJECTIVES: Sutureless aortic valves demonstrated non-inferiority to standard stented valves for major cardiovascular and cerebral events at 1 year after aortic valve replacement. We aim to assess the factors correlating with permanent pacemaker implantation (PPI) in both cohorts. METHODS: PERSIST-AVR is a prospective, randomized, open-label trial. Patients undergoing aortic valve replacement were randomized to receive a sutureless aortic valve replacement (Su-AVR) or stented sutured bioprosthesis (SAVR). Multivariable analysis was performed to identify possible independent risk factors associated with PPI. A logistic regression analysis was performed to estimate the risk of PPI associated to different valve size. RESULTS: The 2 groups (Su-AVR; n = 450, SAVR n = 446) were well balanced in terms of preoperative risk factors. Early PPI rates were 10.4% in the Su-AVR group and 3.1% in the SAVR. PPI prevalence correlated with valve size XL ( P = 0.0119) and preoperative conduction disturbances ( P = 0.0079) in the Su-AVR group. No predictors were found in the SAVR cohort. Logistic regression analysis showed a significantly higher risk for PPI with size XL compared to each individual sutureless valve sizes [odds ratio (OR) 0.272 vs size S (95%confidence interval 0.07–0.95), 0.334 vs size M (95% CI 0, 16–0; 68), 0.408 vs size L (95% CI 0, 21–0.81)] but equivalent risk of PPI rates for all other combination of valve sizes. CONCLUSIONS: Su-AVR is associated with higher PPI rate as compared to SAVR. However, the increased PPI rate appears to be size-dependent with significant higher rate only for size XL. The combination of preoperative conduction disorder and a size XL can lead to a higher probability of early PPI in Su-AVR. Clinical trial registration number: NCT02673697. Abstract : The comparison between sutureless valves and standard stented valves has been investigated in previous studies, demonstrating decreased cross-clamp time using the Perceval prosthesis and similar results for major cardiovascular and cerebral events over the short- to mid-term follow-up [1–3].